Teachers’ Competence in Teaching Civic Education and Its Influence on Students’ Peaceful Attitudes and Security Consciousness in Zamfara State - Sule Muhammad; Manir Jibril (Penerbit Hellow Pustaka, 2026)
This study examined the influence of teachers’ competence in teaching Civic Education on students’ peaceful attitudes and security consciousness in Zamfara State. The research sought to determine the level of teachers’ competence, its effect on students’ peaceful dispositions, and its impact on students’ awareness of security issues. A descriptive survey design was adopted, involving 384 secondary school teachers and students selected through stratified random sampling. Data were collected using a structured questionnaire measuring teachers’ competence, including subject knowledge, pedagogical skills, and classroom management, and students’ outcomes, including peaceful attitudes and security consciousness. Descriptive statistics (means and standard deviations) and inferential statistics (Pearson correlation and multiple regression analysis) were employed to analyze the data and test the hypotheses at a 0.05 significance level. Findings revealed a strong and statistically significant relationship between teachers’ competence and students’ peaceful attitudes (r = 0.62, p < 0.05). Regression analysis further indicated that teachers’ competence significantly predicted students’ security consciousness (B = 0.58, Beta = 0.62) and attitudes toward peace and security (B = 0.63, Beta = 0.65). The study concluded that teachers’ competence is a critical determinant of students’ civic dispositions, peaceful attitudes, and security awareness. The findings highlight the need for continuous professional development, enhanced pedagogical skills, and targeted teacher training to foster peace-oriented mindsets and responsible citizenship among students in insecurity-prone regions.